2013
DOI: 10.1007/s12571-013-0247-y
|View full text |Cite
|
Sign up to set email alerts
|

Food security in rural areas of Limpopo province, South Africa

Abstract: Although South Africa is food secure as a nation, many households remain food insecure. The government has recognized several key food security challenges in the Integrated Food Security Strategy (IFSS). However, South Africa still lacks specific and accepted methods to measure food security and currently has no regulated way of monitoring the food security status of its population. This article reports on an investigation into the food security situation of rural households in the Limpopo Province. Qualitativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
92
5
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 156 publications
(125 citation statements)
references
References 19 publications
(23 reference statements)
14
92
5
1
Order By: Relevance
“…This supports other studies in SSA that found correlations between primary education and food security (FAO 2007;De Cock et al 2013). We found in both countries that the education level of the household head has a significant effect of on household calorific intake (Table 3); in Ethiopia, food security increases as the education level goes up.…”
Section: The Role Of Education and Gender Equalitysupporting
confidence: 90%
“…This supports other studies in SSA that found correlations between primary education and food security (FAO 2007;De Cock et al 2013). We found in both countries that the education level of the household head has a significant effect of on household calorific intake (Table 3); in Ethiopia, food security increases as the education level goes up.…”
Section: The Role Of Education and Gender Equalitysupporting
confidence: 90%
“…The study by De Cock et al (2013) also revealed an important dimension of food insecurity, namely seasonality.…”
Section: Dimensions Of Food Security In Rural South Africa: Seasonalimentioning
confidence: 97%
“…The study by De Cock et al (2013) revealed that only 14.5 % of all respondents declared themselves to be food secure. Even if these data were exaggerated and negatively biased, they suggest that the food insecurity situation remains extremely serious.…”
Section: Measuring and Monitoringmentioning
confidence: 99%
See 2 more Smart Citations